Compromised hippocampus‐striatum pathway as a potential imaging biomarker of mild‐traumatic brain injury and posttraumatic stress disorder. Issue 6 (15th March 2017) - Rangaprakash, D.; Deshpande, Gopikrishna; Daniel, Thomas A.; Goodman, Adam M.; Robinson, Jennifer L.; Salibi, Nouha; Katz, Jeffrey S.; Denney, Thomas S.; Dretsch, Michael N.
Abstract: Objectives: Military service members risk acquiring posttraumatic stress disorder (PTSD) and mild‐traumatic brain injury (mTBI), with high comorbidity. Owing to overlapping symptomatology in chronic mTBI or postconcussion syndrome (PCS) and PTSD, it is difficult to assess the etiology of a patient's condition without objective measures. Using resting‐state functional MRI in a novel framework, we tested the hypothesis that their neural signatures are characterized by functionally hyperconnected brain regions which are less variable over time. Additionally, we predicted that such connectivities possessed the highest ability in predicting the diagnostic membership of a novel subject (top‐predictors) in addition to being statistically significant. Methods: U.S. Army Soldiers ( N  = 87) with PTSD and comorbid PCS + PTSD were recruited along with combat controls. Static and dynamic functional connectivities were evaluated. Group differences were obtained in accordance with our hypothesis. Machine learning classification (MLC) was employed to determine top predictors. Results: From whole‐brain connectivity, we identified the hippocampus‐striatum connectivity to be significantly altered in accordance with our hypothesis. Diffusion tractography revealed compromised white‐matter integrity between aforementioned regions only in the PCS + PTSD group, suggesting a structural etiology for the PCS + PTSD group rather than being an extreme subset of PTSD. Employing MLC, connectivities provided worst‐case accuracy of 84% (9% more than psychological measures). Additionally, the hippocampus‐striatum connectivities were found to be top predictors and thus a potential biomarker of PTSD/mTBI. Conclusions: PTSD/mTBI are associated with hippocampal‐striatal hyperconnectivity from which it is difficult to disengage, leading to a habit‐like response toward episodic traumatic memories, which fits well with behavioral manifestations of combat‐related PTSD/mTBI. Hum Brain Mapp 38:2843–2864, 2017 . ©2017 Wiley Periodicals, Inc.